2018
DOI: 10.1055/s-0038-1669409
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Monitoring Techniques from Patients' and Users' Perspectives

Abstract: Objective  To evaluate preferences from patients and users on 3 uterine monitoring techniques, during labor. Study Design  Women in term labor were simultaneously monitored with the intrauterine pressure catheter, the external tocodynamometer, and the electrohysterograph. Postpartum, these women filled out a questionnaire evaluating their preferences and important aspects. Nurses completed a questionnaire evaluating users' preferences. Results  Of all 52 participating women, 80.8% preferred the electrohyster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Previous research has shown that the EHG technology performs better than TOCO during the first stage of labor in non‐obese and obese women 15 . Furthermore, the technology is preferred by women compared with conventional technologies for UA monitoring 29 …”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that the EHG technology performs better than TOCO during the first stage of labor in non‐obese and obese women 15 . Furthermore, the technology is preferred by women compared with conventional technologies for UA monitoring 29 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, tocodynamometer and intrauterine pressure catheter are conventional devices for monitoring uterine activities, while EHG is an emerging technique. A tocodynamometer measures shape changes in the abdominal wall using a gauge transducer [12] and determines the frequency of contractions but not their intensity [11]. An intrauterine pressure catheter, which is an invasive and current gold standard, directly measures changes in intrauterine pressure using transducer catheters [12].…”
Section: Introductionmentioning
confidence: 99%
“…Electrohysterogram, also called a uterine electromyogram (EMG), measures the electrical activity of uterine muscles through abdominal electrodes [12]. EHG is an alternative technique for noninvasive assessment of uterine contractions resulting from discontinuous bursts of action potentials due to spontaneous electrical discharges from uterine muscles [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] Furthermore, this method and the means of attaching the DU device to the maternal abdomen can be experienced as uncomfortable. 7 Invasive monitoring via FSE is a more reliable method and is considered the criterion standard for FHR monitoring. However, this method carries an increased risk for complications, such as trauma and infection, and can only be applied after membranes have been ruptured and with sufficient dilation.…”
mentioning
confidence: 99%